Managing the Ancestral Way of Life in the Roman Diaspora The Mélange of Philosophical and Scriptural Practice in 4 Maccabees - Tolonen, Anna-Liisa; Uusimäki, Elisa 1986- (2017)
Portrayals of figures of the Israelite narrative are used in 4 Maccabees 1:1-3:18 to discuss the philosophical nature of Judaism. To illustrate the intellectual cultural milieu of the composition, we analyse the notion of (a) ancient philosophy as a way of life and (b) commentary as an intellectual exercise which are part of the author’s lifestyle. He introduces skills of life management into the lives of past figures to promote his notion of virtue. The author (re)casts familiar stories as descriptions of situations in which characters are challenged both rationally and emotionally; thus, he provides the audience with an opportunity for spiritual exercise by means of identification with these characters. This mélange of philosophical and scriptural practice shows that the principles of 4 Maccabees cannot be reduced to either Greek philosophy or Jewish law. Rather, they constitute a philosophical lifestyle which is aligned with both divine law and lived experience.
Keywords: 4 Maccabees -- early Judaism -- Graeco-Roman literature -- ancient philosophy -- commentary culture -- scriptural interpretation -- scriptural figures -- exemplum technique